INDONESIAN LANGUAGE IS THE MOST LANGUAGE USED ON ADVERTISEMENTS IN MEDAN - Maria Olivia Christina Sianipar (Journal MELT (Medium for English Language Teaching), 2020)
This research is discussing about the language that is used most in the names of advertisements on certain areas in Medan. In this era of globalization, many Indonesian people are already good in English, as English as a global language, so it is found some people use English in their activities. Many people use English for the names of their shops, restaurants, hotels, etc. as their advertisement to attract people to get their products. The writer is interested to know about the most language used in some certain areas in Medan. There are some purposes of this research. They are to get the certainty about the percent of Indonesian language usage on advertisements’ names; to get the certainty about the percent of English language usage on advertisements’ names; to get the certainty about the percent of both Indonesian language usage and English language usage on the same advertisements’ names. Here the writer found some results that there are advertisements that using Indonesian language, and some of them using English language and the rest are using both languages they are English language and Indonesian language. The writer is very happy for the result of this research that most of Medan people use Indonesian language for their advertisements.